IMPACT OF THERMAL TREATMENT ON THE PROPERTIES OF THE PROTEIC FOAMS - Alain Riaublanc; Catherine Loisel; Gholamreza Djelveh; Christophe Vial; Irina Nicorescu; Jack Legrand (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The food foams are "whipped" products that have recently experienced significant growth in the food industry. They are appreciated by consumers for their creamy texture, taste and visual aspect. Whey proteins are particularly common ingredients in the formulation of food foams because of their functional properties (foaming properties, interfacial, emulsifying). Denaturation and aggregation of whey proteins further to a heat treatment, allows the improvement of these properties by creating protein aggregates with targeted properties. The objective of this study is to understand the impact of the intensity of heat treatment applied to a protein solution on the aggregation of proteins (proportion, size and morphology of protein assemblies) and on their foaming properties in order to better control the use properties of foamed products stabilized by whey protein aggregates (WPI). In this work, a 2% w/v of whey proteins in the presence of salt (50 mM NaCl) was heated in an Actijoule type tubular heat exchanger at 80, 90 and 100 °C. Native and denatured solutions of WPI were characterized by microcalorimetry ( DSC), size exclusion chromatography (SEC), diffusion light scattering (DLS), electrophoresis (SDS-PAGE), optical microscopy and atomic force microscopy (AFM). To assess the impact of thermal treatment on the foaming ability of protein solutions, a bubbling method has been employed. The experimental results showed that as far as the heating temperature is increased, it promotes the aggregation of proteins into oligomers which then are forming soluble aggregates of about 160 nm in diameter. We have also observed that the increase of this fraction is a continuous function of temperature for solutions treated up to 100 °C. However, the amount of insoluble aggregates formed reaches a maximum when the heat treatment temperature is 90 °C. Finally, we showed by SDS-PAGE that the soluble and insoluble aggregates are stabilized by disulfide bridges and microscopically we found that insoluble aggregates are dense and highly branched. With regard to the foaming properties of proteins, the formation of the foam was very dependent on the thermal treatment applied to protein solutions. Our results demonstrate as well that the time of bubbling is clearly correlated with the proportion of insoluble proteins and for this reason, a thermal treatment at 90 °C that leads to a significant increase of the proportion of insoluble aggregates, retards foam formation. Also,  Lactoglobulin and -Lactalbumin monomers existing in the protein solutions before bubbling, appear to play a crucial role. Thus, we observed that native WPI solutions lead to the formation of dry foams, while the WPI solutions heated to temperatures of at least 80 °C lead rather to the formation of wet foams.